(untitled) (African Journal of Law and Politics, 2025)
This article sets out to ascertain the level of attention that climate change receives under the Cameroonian energy legal and policy framework, more particularly how it supports the development of low-greenhouse gas (GHG) energy or a climate-friendly energy system in Cameroon. The article showcases the climate change implications of energy development in Cameroon and maps the policy guidelines for the development of a low-GHG energy system under the Cameroonian climate change and energy legal and policy instruments. Building on both primary and secondary data and employing the doctrinal research method and the content analysis approach, this article argues that the Cameroonian energy legal and policy framework does not adequately address climate change concerns. The findings reveal that the Cameroonian energy legal and policy frameworks do not adequately support the development of a climate-friendly energy system. Consequently, the potential of the energy sector in contributing to the fight against climate change in terms of mitigation may not be fully tapped. Based on the findings, what is proffered as an important recommendation is the strong need for Cameroon to elaborate and implement holistic energy legal and policy frameworks that comprehensively take on board climate change concerns. Such holistic energy legal and policy frameworks should set targets and timelines for gradual transition from the development of high GHG emissions sources of energy to the development of low or zero GHG emissions sources of energy.